The Influence of Family Finance Socialization and Financial Technology Literacy on Financial Behavior - Nugraheni Ramadhona; Sudarno Sudarno; Muhammad Sabandi (Universitas Negeri Semarang, 2023)
This study aims to determine the effect of financial socialization and financial technology literacy on financial behavior moderated by financial education in students of the Faculty of Teacher Training and Education UNS. This study used a quantitative research type with a population of Faculty of Teacher Training and Education UNS students. The sample was determined as many as 160 samples were taken using a non-sampling technique. The data collection technique uses a five-point Likert scale of 1-5 points distributed via Google Forms. Test the validity of the instrument using Confirmatory Factor Analysis (CFA) and test the reliability using Cronbach Alpha. The hypothesis is tested through Moderated Regression Analysis (MRA) after performing descriptive statistical tests and analysis prerequisite tests. All data was processed using SPSS 25 software. The results of the study proved that there was a significant and positive socialization of family finance and financial technology literacy on the financial behavior of Faculty of Teacher Training and Education UNS students and that financial education could not moderate the socialization of family finance and financial technology literacy on the financial behavior of Faculty of Teacher Training and Education UNS students.